Perhitungan Harga Pokok Produksi dengan Metode Full Costing: Penetapan Harga Jual Produk UKM Ayam Bakar Dapoer Syifa: Calculation of Cost of Production with Full Costing Method: Determining the Selling Price of Dapoer Syifa Grilled Chicken SME Products - Hendri Saputra; Amanda Vinata; Fajar Dwi Cahyo; Adzra Ramadhina; Syifa Fauziah (PT Cakrawarti Empat Proksi, 2026)
This study aims to analyze the calculation of the cost of goods manufactured (COGM) using the Full Costing method and its impact on the selling price at the Syifa grilled chicken SME. The business faces an issue where its production cost calculation fails to incorporate all cost components, potentially leading to an inaccurate selling price. The study employs a descriptive quantitative method with a case study approach. Data were gathered through interviews with the business owner, observation of the production process, and documentation of production costs. The results indicate that the COGM calculated using the company's existing method was Rp 2,275,500 for 100 portions, resulting in a selling price of Rp 22,755 per portion. In contrast, the calculation using the Full Costing method yielded a COGM of Rp 3,560,250 and a selling price of Rp 35,600 per portion. This discrepancy arose because the company's method did not include machinery and equipment depreciation costs in the production costs. Implementing the Full Costing method provides more accurate cost information, thereby assisting the business owner in setting a more appropriate selling price and enhancing the effectiveness of profit management.